Security of organizational changes via operational integration: ensuring methodology - Drobyazko, Svetlana; Potyshniak, Olena; Radionova, Natalia; Paranytsia, Serhii Pavlovych; Nehoda, Yuliia (Generolo Jono Zemaicio Lietuvos Karo Akademija, 2019)
The concept and the need of organizational changes in the corporate environment in order to ensure a lasting effect of economic and strategic security were determined. The methodology for conducting organizational changes based on the use of optimal operational integration, which forms a decomposition of the company’s development goals and forms the field of economic security was proposed. The model analysis of ensuring effective organizational security and operational integration of the functional units of the company was carried out.

Визначено концепцію та необхідність організаційних змін у корпоративному середовищі з метою забезпечення тривалого ефекту економічної та стратегічної безпеки. Запропоновано методологію проведення організаційних змін на основі використання оптимальної операційної інтеграції, яка формує декомпозицію цілей розвитку компанії та формує сферу економічної безпеки. Проведено модельний аналіз забезпечення ефективної організаційної безпеки та оперативної інтеграції функціональних підрозділів компанії.
Keywords: company security; operational integration; organizational changes; company value; business development strategy; functional units; management process; безпека компанії; операційна інтеграція; організаційні зміни; цінність компанії; стратегія розвитку бізнесу; функціональні підрозділи; процес управління